PENGABUH BERAT LABUR DAN KADAR PENGISI PEREKAT TANIN FORMALDEHIDA TERHADAP KETEGUHAN BEKAT LAPIS - adi santoso; rodjak memed; Paribotro sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
It has been known that tannin formaldehyde resin is suitable for exterior plywood adhesive. one of the source of tannin is Acacia decurrens bark. A study on using tannin formaldehyde from. Acacia decurrens bark has been done to predict the effect of glue spread and percentage of filler on the plywood bonding strength. The results show that glue spread has not sigatficant effect on plywood bonding strength, while percentage of filler has significant effect on plywood bonding strength and all plywood resulted meet German Standard requirement for exterior purpose. (AW 100).From the economic paint of view, it is recommended. to use glue spread of 150 g/m2 and percentage of filler of 4o%.